PROSPECTS FOR THE DEVELOPMENT OF GEOLOGICAL TOURISM IN WEST KAZAKHSTAN - Jamilya B. YAKUPOVA; Rysty A. KHALELOVA; Ainur K. KHAIRULLINA; Nursulu S. ZHARMAGANBETOVA; Gulbakhit Zh. ABDUSHEVA (Geo Journal of Tourism and Geosites)
Paleontology is an important and integral branch of geology and is an important scientific discipline that helps to better understand the history of life on Earth. The popularization of paleontology is currently based on fossil finds. The purpose of this work was to identify potential locations for paleontological tourism in Western Kazakhstan. The materials were studied using the experience and techniques used in classical paleontology. The article discusses the possibility of developing paleontological tourism in Western Kazakhstan. A description of the main locations of natural locations of fossils of invertebrate and vertebrate organisms is given, such as the village of Pogodaevo, the Aktolagai Cretaceous Plateau, Akkegershin, the Kara Bala-Kan Temir necropolis, the Koi-Kara, Iman-Kara mountains, the Sululy Kapy gorge, the tracts of the Mangistau region, and places are given storage of fossils, inspection and study of paleontological finds. A model of paleontological tourism is proposed. The role of paleotourism among the population has been determined by conducting sociological research. In general, Western Kazakhstan has the prospect of developing paleontological tourism of an excursion and educational nature. For this purpose, the region has a large number of resources and various local history and environmental museums containing paleontological materials.